2014
DOI: 10.1590/0037-8682-0021-2014
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of class 1 integrons in Klebsiella pneumoniae clinical and microbiota isolates belonging to different phylogenetic groups in Recife, State of Pernambuco

Abstract: Introduction:The high prevalence of Klebsiella pneumoniae infections is related to the ability of K. pneumoniae to acquire and disseminate exogenous genes associated with mobile elements, such as R plasmids, transposons and integrons. This study investigated the presence of class 1 integrons in clinical and microbiota isolates of K. pneumoniae belonging to different phylogenetic groups and correlated these results with the antimicrobial resistance profi les of the studied isolates. Methods: Of the 51 isolates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 32 publications
3
16
0
Order By: Relevance
“…So far, various gene cassettes encoding phenotypic resistance to antibiotics have been found in integrons (4). As an example, genes encoding resistance to streptomycin and trimethoprim are remarkably associated with class I integrons (28). Similarly, in our study, a significant correlation was observed between resistance to co-trimoxazole, strep-tomycin, and ceftazidime with class I integrons, which indicates the association of resistant genes with this class of integron.…”
Section: Discussionsupporting
confidence: 85%
“…So far, various gene cassettes encoding phenotypic resistance to antibiotics have been found in integrons (4). As an example, genes encoding resistance to streptomycin and trimethoprim are remarkably associated with class I integrons (28). Similarly, in our study, a significant correlation was observed between resistance to co-trimoxazole, strep-tomycin, and ceftazidime with class I integrons, which indicates the association of resistant genes with this class of integron.…”
Section: Discussionsupporting
confidence: 85%
“…Our results indicate that only eight isolates were positive for class I integrons, while class II and class III integrons were not detected in any of the isolates. This finding is comparable to those of Lima et al 60 and Ashayeri et al 61 . Class III integrons have been reported only in very few studies 14,62,63 .…”
Section: -59supporting
confidence: 92%
“…A study conducted in the USA reveals that the prevalence of class 1 integron was about 70% in Klebsiella spp. (23), another study which compared the prevalence of class 1 integron among microbiota and clinical isolates imparted that there is no class 1 integrons in microbiota, whereas in clinical isolates of Klebsiella pneumoniae 47% were with Kp I and 14.3% with Kp III group of class 1 integrons (24). In this study, class 1 integrons (intI1) were amplified in 42% of the isolates and integron gene cassette in 60% of the class 1 integron positive colistin-resistant K. pneumoniae were identified.…”
Section: Discussionmentioning
confidence: 99%